Edukasi Manajemen Pengendalian Obesitas pada Remaja - Ariyanto, Ariyanto; Fatmawati, Tina Yuli; Efni, Nel (Universitas Baiturrahim, 2024)
Obesity is an accumulation of excess triacylglycerol in fat tissue due to excess energy intake compared to its use. The prevalence of obesity has increased significantly throughout the world, both in developed and developing countries. Factors such as lifestyle changes, high-calorie diets, lack of physical activity, and urbanization are contributing to this increase. A diet that tends to consume less vegetables and fruits, consumption of fried/fatty/coconut milk foods, sweet drinks and fast food containing processed products is often found in adolescents. The purpose of this service is to increase knowledge in managing obesity control in adolescents at SMA N 13 Jambi City. The activities were carried out at SMAN 13 Jambi City, taking place in the classroom, from April to August 2023 with a target number of 22 students. Methods community service activity include lectures, discussions, demonstrations in anthropometric measurements. The results of the activity showed that there was an increase in teenagers' knowledge about obesity management, teenagers were able to detect obesity early and were able to calculate BMI independently. The conclusion in this community service activity is health education can increase adolescents' knowledge about obesity control management